Acadlinker : Design and Evaluation a Skill-Based Student Network with a Touch of AI - Nalawade, Vinay; Bhandare, Swamini; Bhole , Sumit; Bhongale, Vaishnavi; Ghayal, Mayur (International Journal of Recent Advances in Engineering and Technology, 2025)
Acadlinker is a web-based application that facilitates academic networking among students across different colleges within the same university. The platform allows users to create detailed profiles showcasing their academic and skill-based information, connect with peers through friend requests, and engage in secure chats with file and code-sharing capabilities. It further supports group formation for projects and study sessions, along with the option to share posts containing documents or media files accessible to friends. The system integrates real-time notifications for friend requests, group invitations, and post interactions, while offering a skill-based friend-finder feature to encourage meaning ful academic collaboration. Acadlinker provides a secure, academic-focused environment designed to foster collaboration, networking, and skill development among students.